Novostavba kostela v obci Krhová - Ječmen, Marek (Vysoké učení technické v Brně. Fakulta architektury)
Předmětem diplomové práce je návrh novostavby katolického kostela ke stávajícímu hřbitovu v obci Krhová u Valašského Meziřící. Hlavní myšlenkou je dát obci stavbu, která z historického hlediska byla vždy stavbou nejdůležitější. Stavba, která reprezentuje hodnoty trvalé. Objekt kostela s hřbitovem je komponován jako horizontála hřbitovní zdi, z níž vystupuje jednoduchá vertikální forma kostela, která se tyčí nad obcí.

The subject of this thesis is design the new building of Catholic church which is connected to current cemetery in the village of Krhová near Valasske Mezirici. The idea is to give the community building, which from historical point of view has always been the most important building. The building, which represents the permanent values. The church and cemetery are composed as horizontal cemetery wall, from which a simple vertical form of the church that towers above the village.
New Church in Krhova
Keywords: kostel; Krhova; hrbitov; krajina; church; Krhova; cemetery; landscape